2020
DOI: 10.7554/elife.59469
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic activation modulates the signal from the Reissner fiber to cerebrospinal fluid-contacting neurons during development

Abstract: The cerebrospinal fluid (CSF) contains an extracellular thread conserved in vertebrates, the Reissner fiber, which controls body axis morphogenesis in the zebrafish embryo. Yet, the signaling cascade originating from this fiber to ensure body axis straightening is not understood. Here, we explore the functional link between the Reissner fiber and undifferentiated spinal neurons contacting the CSF (CSF-cNs). First, we show that the Reissner fiber is required in vivo for the expression of urp2, a neuropeptide ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 55 publications
(102 reference statements)
2
52
1
3
Order By: Relevance
“…It has been found that scospondin mutant embryos lacking the Reissner fibre fail to extend a straight body axis during embryonic development [45,46]. Interestingly, the Reissner fibre appears to be required for the expression of urp2 in CSF-contacting neurons [13,14], which is in agreement with recent findings showing that it is functionally coupled to the mechanosensory function of CSF-contacting neurons [49]. The Reissner fibre is highly conserved and present in the central canal of almost all vertebrate species [48] including X. laevis [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that scospondin mutant embryos lacking the Reissner fibre fail to extend a straight body axis during embryonic development [45,46]. Interestingly, the Reissner fibre appears to be required for the expression of urp2 in CSF-contacting neurons [13,14], which is in agreement with recent findings showing that it is functionally coupled to the mechanosensory function of CSF-contacting neurons [49]. The Reissner fibre is highly conserved and present in the central canal of almost all vertebrate species [48] including X. laevis [50].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with those of UII, the functions of Urps are much less understood. However, recent studies in zebrafish (Danio rerio) have shown that Urp1 and Urp2 play a critical role in spine morphogenesis [12][13][14].…”
mentioning
confidence: 99%
“…And What is its function? In the last few years, RF has been studied using new methodological approaches, such as tandem mass spectrophotometry [ 35 ] and mutant zebrafish lines [ 29 , 33 , 34 , 36 , 37 , 148 ], providing some insight on these historical questions.…”
Section: Reissner Fiber: Composition Formation and Movementmentioning
confidence: 99%
“…Transcriptomic analysis of sspo zebrafish mutants [ 36 , 148 ] revealed high downregulation of urotensin neuropeptide 2 (Urp2). This peptide is secreted in the spinal cord by ventral cerebrospinal fluid-contacting neurons (CSFcNs), a group of mechanosensory neurons that extend motile cilia and microvilli toward the central canal that will eventually contact the RF, detecting the spinal curvature in a directional manner (Fig.…”
Section: Function Of the Sco Sco-spondin And Rfmentioning
confidence: 99%
“…When the axis is straight, RF floats in the neural canal, but when it curves comes into contact with mechanosensory neurons in the neural tube’s inner wall that activate axial musculature, restoring the body’s stiffness axis ( Orts-Del’Immagine et al, 2020 ). Two further articles have shed additional insight into RF- CSF-cn mechanosensory transduction ( Cantaut-Belarif et al, 2020 ; Lu et al, 2020 ). These studies showed that URP requires an intact RF to be expressed and is downregulated in SCO-spondin mutants, which results in impaired signaling to trunk muscles.…”
Section: Hypotheses About Rf’s Functionsmentioning
confidence: 99%